Safety of Tattoos and Permanent Make up (PMU) Colorants - Eleni Andreou; Sophia Hatziantoniou; Efstathios Rallis; Vasiliki Kefala (Cosmetics, 2021)
The art of tattooing is a popular decorative approach for body decoration and has a corrective value for the face. The tattooing procedure is characterized by placing exogenous pigments into the dermis with a number of needles. The process of creating traditional and cosmetic tattoos is the same. Colorants are deposited in the dermis by piercing the skin with needles of specific shape and thickness, which are moistened with the colorant. Colorants (pigments or dyes) most of the time include impurities which may cause adverse reactions. It is commonly known that tattoo inks remain in the skin for lifetime. It is also a fact that the chemicals that are used in permanent makeup (PMU) colorants may stay in the body for a long time so there is a significant long-term risk for harmful ingredients being placed in the body. Tattoo and PMU colorants contain various substances and their main ingredients and decomposition components may cause health risks and unwanted side effects to skin.